Secretion of Acetylxylan Esterase From Chlamydomonas reinhardtii Enables Utilization of Lignocellulosic Biomass as a Carbon Source - Ramos-Martinez, Erick Miguel; Fimognari, Lorenzo; Rasmussen, Maria K.; Sakuragi, Yumiko (Frontiers in Bioengineering and Biotechnology, 2019)
Microalgae offer a promising biological platform for sustainable biomanufacturing of a wide range of chemicals, pharmaceuticals, and fuels. The model microalga Chlamydomonas reinhardtii is thus far the most versatile algal chassis for bioengineering and can grow using atmospheric CO2 and organic carbons (e.g., acetate and pure cellulose). Ability to utilize renewable feedstock like lignocellulosic biomass as a carbon source could significantly accelerate microalgal based productions, but this is yet to be demonstrated. We observed that C. reinhardtii was not able to heterotrophically grow using wheat straw, a common type of lignocellulosic biomass, likely due to the recalcitrant nature of the biomass. When the biomass was pretreated with alkaline, C. reinhardtii was able to grow using acetate that was released from the biomass. To establish an eco-friendly and self-sustained growth system, we engineered C. reinhardtii to secrete a fungal acetylxylan esterase (AXE) for hydrolysis of acetylesters in lignocellulosic biomass. Two transgenic strains (CrAXE03 and CrAXE23) secreting an active AXE into culture media were isolated. Incubation of CrAXE03 with wheat straw resulted in eight-fold increase in the algal cell counts with concomitant decreases of biomass acetylester contents by 96%. The transgenic lines showed minor growth defects compared to the parental strain, indicating that secretion of the AXE protein impose limited metabolic burden. The results presented here would open new opportunities for applying low-cost renewable feedstock, available in large amounts as agricultural and manufacturing by-products, for microalgal cultivation. Furthermore, acetylesters, and acetate released from them, are well-known inhibitors in lignocellulosic biofuel productions; thus, direct application of the bioengineered microalga could be exploited for improving renewable biofuel productions.